The effect of vibrational disturbances on heat and hydrodynamic processes in a melt during the crystal growing by the Bridgman method - Fedorov, O.P.; Demchenko, V. F.; Shuba, I.V.; Zhyvolub, E. L. (Reports of the National Academy of Sciences of Ukraine, 2015)
The effect of vibrational disturbances on the heat and mass transfer during the directional solidification using the Bridgman technique has been studied. The mathematical simulation and direct observations of the solid–melt interface have been used.